Obstacles Facing Promoting Tourism for Islamic Landmarks from the Perspective of Tour Operators in Egypt - Hassan, Suzan Bakri (Graduate School, Universitas Brawijaya, 2015)
The UNESCO launched a campaign #unite4heritage in Egypt to defeat extremism and intolerance. The message of such campaigne is peace, dialogue and unity embedded in cultural heritage. As culture and tourism are linked together, such message could be delivered through improving culture heritage tourism in Egypt. Islamic landmarks are considered as a part of human heritage. Therefore, the purpose of this study is to identify how much tour operators in Egypt include Islamic landmarks in their programs to determine the obstacles facing promoting cultural tourism in Islamic landmarks' areas. Additionally, the study would identify positive results in the case of developing heritage tourism in Egypt. To achieve a high result, a survey approach was employed to collect data from 100 tour operators, using a completed questionnaire technique as well as a Likert Scale and statistical models in order to test and interpret the research outcomes. The research findings indicated that although tour operators in Egypt are convinced of the significance of the Islamic landmarks, there is no contradiction between creating global understanding and at the same time achieving benefit to the local community. However, there is a range of obstacles facing promoting such type of tourism in Egypt. Keywords: Culture heritage tourism, community, Egypt, Islamic civilization.